Management control systems - Anthony, Robert N.; Dearden, John; Bedford, Norton M. (Homewood, Ill. : R.D. Irwin, 1984)
This fifth edition of the book follows closely the format of the fourth. All of the text, however, has been rewritten to incorporate new findings from the literature and observations from practice. The book is designed for a one-semester course for students who have had a course in management accounting and who wish to study management control in greater depth.
Includes bibliographical references and index.
hza 05/09/2018
Loans
Keywords: Industrial management; Cost control